Efficacy and safety of IL-23 p19 inhibitors in the treatment for inflammatory bowel disease: a systematic review and meta-analysis - Wang, Shuhan; Sun, Hui; Wang, Qian; Xiao, Han (Frontiers in Pharmacology, 2025)
BackgroundThe treatment outcomes of inflammatory bowel disease (IBD) have been significantly improved by the advent of new biologics, including ulcerative colitis (UC) and Crohn’s disease (CD), particularly for refractory cases. However, the growing number of therapeutic options has also complicated clinical decision-making regarding drug selection and switching. The overall performance of IL-23 p19 inhibitors for the treatment of IBD was evaluated by the systematic review and meta-analysis in this study.ObjectiveThe objective of this study was to combine the multiple indicators to accurately evaluate the efficacy and safety of IL-23 p19 inhibitors, aimed to offer an insight into the development of clinical physicians’ medication.MethodsA comprehensive literature review on PubMed, Embase, Web of Science, and Cochrane Library until June 2024 was conducted in this study, which mainly focused on the randomized controlled trials (RCTs) to evaluate the IL-23 p19 inhibitors within adult patients with UC or CD. Additionally, the clinical outcomes, endoscopic findings, histological assessments, and safety profiles were aggregated and subjected to analysis by a random-effects model.ResultsTwenty-five RCTs [15 CD, 10 UC] were involved in this study, and it was revealed that IL-23 p19 inhibitors showed significant effects on clinical remission (CR) in IBD, regardless of induction or maintenance treatment (CD, induction: risk ratio [RR] 1.95, 95% confidence interval [CI] 1.71–2.23; I2 = 0%, p = 0.68; UC, induction: RR 2.69, 95% CI 1.80–4.03; I2 = 50%, p = 0.09; CD, maintenance: RR 1.24, 95% CI 1.04–1.48; I2 = 0%, p = 0.57; UC, maintenance: RR 2.62, 95% CI 0.92–7.49; I2 = 42%, p = 0.19), and the risk of adverse events (AEs) was similar to that of placebo (CD, induction: RR 0.88, 95% CI 0.82–0.94; I2 = 2%, p = 0.41; UC, induction: RR 0.92, 95% CI 0.82–1.03; I2 = 0%, p = 0.54; CD, maintenance: RR 1.00, 95% CI 0.89–1.13; I2 = 29%, p = 0.25; UC, maintenance: RR 0.96, 95% CI 0.87–1.06; I2 = 0%, p = 0.44).ConclusionIn IBD treatment, IL-23 p19 inhibitor therapy exhibited effective functions in the inducement and maintenance of clinical and endoscopic remissions, as well as in some histological cases.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024569807, identifier CRD42024569807